THE EFFECTIVENESS OF IMPLEMENTATION WARMER APPERCEPTION TO CONSTRUCT THE CONCEPTUAL UNDERSTANDING ON THE LEARNING MATERIAL OF VECTOR - Rohmah, Riska Nur; Utomo, Dwi Priyo; Zukhrufurrohmah, Zukhrufurrohmah (MEJ (Mathematics Education Journal), 2019)
One of the learning stages is apperception. Warmer apperception is an activity that conducted to make the students? knowledge to be stored in long-term memory. This research aimed at: 1) describing the learning implementation using Warmer apperception to construct a conceptual understanding in the vector material, 2) determining the effectiveness of the implementation of Warmer apperception to construct a conceptual understanding in the vector material. The effectiveness of learning using Warmer apperception could be seen from: 1) the observation of learning implementation using Warmer apperception that indicated a minimum of the sufficient category; 2) the students? response questionnaire indicated a minimum of positive response category; and 3) the test results of students? conceptual understanding indicated a minimum of quite a good category. The subjects of this research were the students of 10th grade of Mathematics and Natural Science (MIA) at Senior High School (SMA) of Muhammadiyah 3 Batu, in which it consisted of 21 students. Based on the research conducted, it was obtained that the observation results of learning implementation using Warmer apperception got a very good category, the questionnaire results obtained a positive response category, and the test results of students? conceptual understanding got a quite good category. Thus, the implementation of Warmer apperception to construct a conceptual understanding of the vector material is effective..